Reconstruction of regional regulations on the development of natural tourism and river water tourism in the Muria mountains based on sustainable tourism - Hernanda, Trias; Azizah, Naili; Syaharani, Pramitha Putri; Budiono, Arief (Edelweiss Applied Science and Technology, 2024)
The potential for developing nature-based tourism and water tourism in Kudus Regency has quite good potential, but its development is not yet in line with the principles of sustainable tourism. This is also supported by regional regulations that have not fully implemented sustainable tourism. This research uses normative research methods by conducting a study of the synchronization of legal regulations, namely regional laws and regulations with the principles of sustainable tourism and ecological justice. The first result of this research is the threat of environmental damage and a pollution crisis that will occur in the Mount Muria area, if it is not followed up with special regional regulations, second, ecological justice is needed in the substance of regional regulations based on sustainable tourism, third, the concept of new regional regulations must contains the substance of sustainable tourism, green economy and ecological justice.